Comparative Analysis of Quan and Watanabe Pan‐Coronavirus Assays for Bat Coronavirus Diversity in Sarawak, East Malaysia - Sultana Parvin, Habeebur-Rahman; Faisal Ali, Anwarali Khan; Mohd Azlan, Jayasilan; Melvin, Gumal; Tan, Cheng Siang (John Wiley & Sons, Inc, 2025)
Bats are natural reservoirs for a diverse range of coronaviruses (CoVs), including those closely related to SARS‐CoV and SARS‐CoV‐2, making them crucial for understanding CoV genetics and zoonotic transmission. The exceptional bat diversity inSarawak, Malaysian Borneo, provides an ideal setting to investigate CoV diversity and potential transmission pathways. Thisstudy examined CoV prevalence and diversity in 346 fecal samples from bats across 29 species in northern and westernSarawak, employing two pan‐CoV PCR assays: Quan (Q‐assay) and Watanabe (W‐assay). The Q‐assay and W‐assay estimatedthe CoV prevalence to be 14.45% and 12.72%, respectively. The overall true prevalence based on both assays was 22.83%. Therewas a fair agreement between both assays (κ = 0.286) with comparable performance in detecting the virus (McNemar p > 0.05).Phylogenetic analyses identified six distinct clades within alphacoronaviruses (α‐CoVs) and betacoronaviruses (β‐CoVs),comprising two unclassified Borneo‐Alpha CoVs and four from the subgenera Minunacovirus, Rhinacovirus, Nobecovirus, andSarbecovirus. This study represents the first report of Sarawak bat CoVs derived from rectal and fecal samples, addressing asignificant knowledge gap. The findings highlight the need for complementary molecular assays to enhance CoV surveillanceand deepen understanding of viral ecology in regions of high biodiversity, with implications for zoonotic disease prevention.